Second Language Learning in Older Adults: Effects on Brain Structure and Predictors of Learning Success - Nilsson, Jonna; Berggren, Rasmus; Garzón, Benjamín; Lebedev, Alexander V.; Lövdén, Martin (Frontiers in Aging Neuroscience, 2021)
It has previously been demonstrated that short-term foreign language learning can lead to structural brain changes in younger adults. Experience-dependent brain plasticity is known to be possible also in older age, but the specific effect of foreign language learning on brain structure in language-and memory-relevant regions in the old brain remains unknown. In the present study, 160 older Swedish adults (65–75 years) were randomized to complete either an entry-level Italian course or a relaxation course, both with a total duration of 11 weeks. Structural MRI scans were conducted before and after the intervention in a subset of participants to test for differential change in gray matter in the two groups in the inferior frontal gyrus, the superior temporal gyrus, and the hippocampus, and in white matter microstructure in the superior longitudinal fasciculus (SLF), inferior longitudinal fasciculus (ILF), fronto-occipital fasciculus, and the hippocampal (HC) section of the cingulum. The study found no evidence for differential structural change following language training, independent of achieved vocabulary proficiency. However, hippocampal volume and associative memory ability before the intervention were found to be robust predictors of vocabulary proficiency at the end of the language course. The results suggest that having greater hippocampal volume and better associative memory ability benefits vocabulary learning in old age but that the very initial stage of foreign language learning does not trigger detectable changes in brain morphometry in old age.